2020
DOI: 10.5588/ijtld.19.0734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of comorbidities on quality of life in Filipino people with tuberculosis

Abstract: BACKGROUND: We investigated health-related quality of life (HrQoL) in Filipino people undergoing TB treatment, and whether HrQoL was negatively impacted by comorbidity with undernutrition, diabetes (DM) and anaemia.METHODS: Adult participants were enrolled in public facilities in Metro Manila (three sites) and Negros Occidental (two sites). Multivariate linear regression was used to model the four correlated domain scores from a WHOQOL-BREF questionnaire (physical, psychological, social, environmental). A for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Studies have found that comorbidities such as undernutrition or diabetes mellitus (DM) impact the TB care cascade [ 76 , 77 ]. For other diseased conditions, comorbidities or concomitant treatment is prognostic of lower QoL scores, especially in the physical domain [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that comorbidities such as undernutrition or diabetes mellitus (DM) impact the TB care cascade [ 76 , 77 ]. For other diseased conditions, comorbidities or concomitant treatment is prognostic of lower QoL scores, especially in the physical domain [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…TB co-infection worsens the symptoms of HIV and advances the disease to the next stage, which can further deteriorate the HRQoL [ 70 ]. Additionally, studies have found that TB patients are negatively impacted by comorbidities such as undernutrition, diabetes mellitus (DM), anemia, or HIV infection [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of the PLWTB in this study were newly diagnosed PLWTB in the intensive phase (first 2 months) of their treatment. The intensive phase can be physically and socially excruciating for PLWTB receiving TB treatment for the first time thus could negatively affect their QOL [53]. Previous studies emphasise the relevance of social support to the ability of PLWTB to cope with the impact of TB on their lives [23,54,55] and faith-based or religious institutions play a key role in providing this social support to PLWTB globally [22].…”
Section: Plos Onementioning
confidence: 99%
“…Those with a higher BMI (>18.5) showed a lower mortality rate compared to those with lower BMI [13]. By addressing nutrition as an important determinant of pathogenesis and outcome of TB treatment, the health-related quality of life can be improved [14]. The genetic component linked with the pathogenesis of TB is less studied but has been well reported by a study [15].…”
Section: Discussionmentioning
confidence: 99%